Broadband solar absorption by chromium metasurface for highly efficient solar thermophotovoltaic systems. (January 2023) - Rana, Ahsan Sarwar; Zubair, Muhammad; Chen, Yifan; Wang, Zeng; Deng, Jie; Chani, Muhammad Tariq Saeed; Danner, Aaron; Teng, Jinghua; Mehmood, Muhammad Qasim
Abstract: We report a broadband metasurface solar absorber composed of refractory material chromium (Cr) for the intermediate structure of a solar thermophotovoltaic (STPV) system that can overcome the Shockley–Queisser limit for efficient solar energy harvesting. The metasurface absorber exhibits high broadband absorptance with an average higher than 90% for 300–1200 nm. The self-passivation property of chromium ensures resistance to oxidation and corrosion, besides the benefit of being a low-cost material having stability at higher temperatures. The proposed absorber forms one part of the intermediate structure, whereas the emitter forms its second part. The emitter shapes the incoming electromagnetic (EM) waves to have energies just above the PV cell bandgap to assist in efficient electron-hole pair generation. The proposed STPV system can achieve PV cell efficiency of 43.2% with an efficiency greater than 42% in a broad color temperature range of 1597–2573 K, which is comparable to the state-of-the-art. The innovation in our work comes from efficiency enhancement through the hybridization of selectivity and broadband response of the proposed absorbers and emitter. The designs are also subjected to detailed analyses to understand the mechanism behind their performance. Moreover, a robustness check is performed to know which design parameters are crucial to acquiring such results. Highlights: Multiple highly efficient solar absorbers having simple geometries are reported. High STPV efficiency of 43.2% can be achieved by employing an emitter with hybrid emission. The absorber and emitter pair is analyzed using various approaches. Dielectric coatings can be used to increase thermal stability without compromising efficiency. The proposed STPV system is suitable for a wide energy range of 0.35–0.67 eV.